Analisis Penerapan Blue Ocean Strategy pada PT Sofyan Hotels,Tbk - Atika Riasari (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2020)
This research aims to identify the suitability of the strategy adopted by Sofyan Hotels with the concept of blue ocean strategy and analyze the effectiveness of the strategy adopted by Sofyan Hotels. The method in this study was 25 points which will be used as indicators and instruments of variable A which is a strategy of the companies studied to variable B which is characteristic of the blue ocean strategy. Research results obtained from comparing the 25-point characteristics of strategic blue ocean with the company's strategy was obtained suitability as much as 25 points or have a degree of conformity of 100% means the strategy Sofyan Hotels accordance with the principles of the strategy blue ocean and this concept as a form of applying the blue ocean strategy proved effective in today's business competition. Sharia hotel that was not considered by competitors succeeded in creating new markets for Sofyan Hotels currently has 19 hotels with 1775 rooms spread throughout Indonesia. With the strategy adopted, the gain Sofyan Hotels grew by an average 7.72% per year and managed to win the World's Best Family Friendly Hotel in 2015.